BODY SATISFACTION AMONG PRESCHOOLAGE CHILDREN IN CARINTHIA (AUSTRIA) - Jenull, Brigitte; Salem, Ingrid (European Scientific Journal, ESJ, 2015)
Worldwide, the prevalence rates of overweight and obese children has significantly increased over the last decades. Evidence suggests that overweight and obesity may lead to serious health hazards such as diabetes mellitus typ 2, cardiovascular diseases or problems of the muscosceletal system. Therefore it is important to analyse biological, social and psychological causes of overweight. The objective of this paper was to explore the prevalence of overweight and obesity in preschool-age children and their parents as well as to discuss possible risk factors, like nutritional and recreational habits, body satisfaction, sleep duration and media consumption, associated with overweight. We conducted a cross-sectional study among 319 children aged three to six years and their parents (n = 257) in the city of Villach, Austria. Results show that the majority of children had normal weight, although one third of the mothers and more than half of the fathers were overweight or obese. Sporty children preferred vitamin-rich foods whereas children with high media consumption time liked sugary foods. In families with lower socioeconomic background, children spent significantly more time watching television. Parents can play a central role by limiting media consumption or determining their childrenÂ´s bedtime. Our analysis highlights that only 22% of preschool children are satisfied with their bodies, most of them wanting to be thinner. Thus, thinness is highly valued in our society, even among the youngest. Interventions to prevent overweight have to focus on the parental-child interaction and the home setting as well as educational and societal aspects.